Counter argumentation against the theory of discrediting hadith as linguistic evidence while accepting the authenticity of anomalous qira ʾat and unknown poetry - Yaacob, Solehah@Nik Najah Fadilah (Brill, Netherlands, 2016)

(untitled)
Linguistic argumentation, according to Arab grammarians means a formulation of grammatical rules from the primary sources, which are; Anomaly, consensus, measurement, the argumentation which bases on circumstances and others. The anomaly sources are considered the most authentic references which are Quran, Hadith an-Nabawi and Arabic poetry. The research aims to highlight the differing views of some Arab grammarians in devising the grammatical rules of the hadith. The Quran has no need to debate on its authenticity due to the reliable reading of all verses consisted. However the questions raise; what is the difference between reliable reading and anomalous reading? Why grammatical rules which derived from anomalous reading were accepted? And why the linguistic argumentation which resulted from Hadith an-Nabawi was refuted? And why it was accepted in unknown poetry? And why the argumentation from Quran and Arab poetry are not enough as evidences in linguistic argumentation? These questions will be answered thoroughly by presenting the evidences and arguments from the scholars. An analytical study will develop the method approach of the topic discussion.